(untitled) (Research, Society and Development, 2021)
In the process of discovering and revealing sexual orientation, the term outness is used to refer to the act of recognizing oneself as a homosexual, while the term coming out is synonymous with what is known as “coming out of the closet” or coming out as a homosexual in society and the family. In this context, the disclosure of sexual orientation may come to manifest as a problem in personal relationships, especially within the family. This is a qualitative, descriptive and exploratory study, of the type of experience report, using the Snowball method as a strategy for accessing the sources. To identify the participants, a cis gay man, called “Seed”, was asked to indicate two men also cis gay, who had different experiences in the assumption of their sexuality within the family. Two reports were obtained, identified as “Report 1 – Blue” and “Report 2 – Red”. As for the assumption of her sexuality, Azul reported that she did not interfere much in her relationship with her family. And that the relationship has always been one of self-exclusion, being excluded by family members as well. Vermelho says that the process of assuming his sexuality did not interfere in his relationship with family members, and that in the beginning, there was a period of adaptation and construction of mutual respect between him and his mother and with his sister and brother, nothing changed. This study may support discussions related to the influence of family reactions and bonds in the process of discovering the individual’s sexual orientation, as well as in their behavior towards the family and society.